O "espetáculo do cabra macho" : um estudo sobre os vaqueiros nas vaquejada no Rio Grande do Norte - Aires, Francisco Janio Filgueira (2008)
This body of work discusses the gender meanings associated with cowboys while endorsing contemporary rodeos in Rio Grande do Norte as a recreational sport and a form of ludic expression. As a result, this research has focused on rodeo practices, aiming to understand the different aspects emphasizing masculinity: these associations being constructed through relationships, contexts and the competitiveness between participants. These gender meanings hinge on the desire for a wining performance and on the behaviour exhibited among cowboys outside the competitive ring in specific social settings such as parties and recreational time. The latter were the focus of the ethnographic research; direct observation and semistructured interviews with cowboys in rodeo stadiums were also used. Through qualitative analysis of the collected data, it was revealed that historically and socially different trajectories do not immediately cause a gender crisis in cowboys, but the assignment of new significance by the social acts in each historical context. However, the presence of cowboys leads to other models of masculinity configured by expressions and the insertion of new personas, not coming directly from field activities, but imbued by the symbolic elements of the cowboy persona, constructed throughout history